Effect of Diffusers Installation in Inlet Primary Air Coal Pulve - R. Panji Satrio Wening Galih; Bambang Arip Dwiyantoro (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2022)
This paper investigates the effect of installing several diffuser models in the pulverizer ZGM123-GII inlet ducting on air flow characteristics and wear concentration. Results of the internal check found that an area of the wall and the surrounding components were wearing abnormally or faster than usual. This condition will affect the availability of the pulverizer. There are 6 variations model used in this study to solve this problem. The 2 variations in the number of blade, there are 2 and 3 blades, combined with 3 angle variations, namely 30o, 45o, and 50o. In this study, the viscous k-omega SST model was used to simulate airflow from the primary inlet to the area above the throat ring. The results show the contours of velocity of the air and the velocity vector on the pulverizer. Model with an angle of 45 degrees and the number of blade 3, is able to circulate air dominantly on the left side of the primary air inlet ducting, according to the reference study. From all variations, the model 45o angle with 3 blades and 50o angle with 3 blades are able to overcome the wear concentration problem.